Strategi Pemasaran Sapi Potong Berdasarkan Tinjauan Studi Literatur - Atsiilah Dwi Kurnia P; Mawar Petriani S; Helmi Naufal A; Wien Kuntari (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Marketing plays a crucial role in the development of beef cattle farming businesses in Indonesia. An effective marketing strategy is the key to ensuring good product acceptance and satisfying consumers. The objectives of this research are: (1) understanding consumer needs and preferences; (2) identifying effective marketing strategies; and (3) using resources more efficiently. In this research, the literature study method is used as the main approach, by analyzing various relevant sources to collect the necessary information. The results of the literature review reveal important findings regarding beef cattle marketing strategies. Market segmentation is an important first step in meeting the needs and desires of the target market segment. After segmentation, determining the target market is the next step to ensure resources can be optimized and marketing strategies can achieve the set goals. Determining product positioning through positioning is the key to differentiating products from competitors by building uniqueness and added value. Overall, marketing plays a central role in maintaining the success and growth of beef cattle farming businesses. By implementing the right marketing strategy, companies can increase product acceptance, satisfy consumers, and strengthen their position in the market. In identifying beef cattle marketing, there are two opportunities that will be presented, including: (1) getting new ideas for marketing, and (2) understanding competitors' strategies to increase the market.